INCREASING NON-AERONAUTICAL REVENUE FROM BUSINESS IN TRANSIT ORIENTED DEVELOPMENT (TOD) M1 SOEKARNO-HATTA INTERNATIONAL AIRPORT (The Indonesian Journal of Business Administration, 2019)
Angkasa Pura II’s revenue divided into aeronautical revenue, and non-aeronautical revenue. Based on company strategic objective, namely is Giant Dream 2020, one of the company objectives in 2020 is achieving revenue ? IDR 14,7 Trillion and Non-Aeronautical contribution 50-60% with good risk management. Based on the performance company in 2018, there are still a gap to reach company’s goal in 2020.  The revenue’s gap which is ± Rp.5,2 trillion, and the non-aeronautical gap contribution still ± 13-20% from expected proportion of non-aeronautical revenue contribution. Production achievement of Non-Aeronautical Business 2018 reaches 95%. However, if production is reached 100%, it is still hasn’t achieved the target. The research objective based on the business issue above, to find out non-aeronautical business still has the potential to be developed in order to increasing non-aeronautical revenue.To solve the business issue, to find business potential, author doing situation analysis and elaborate of segmentation Non-Aeronautical revenue to find business that has potential and can be develop, and author finding those are potential business in Transit Oriented Development (TOD) M1 Soekarno-Hatta International Airport. Author conducted survey. to find out which commercial facilities are most needed by TOD M1 users, and to find out what facilities need to be improved. Service Quality Survey (Servqual) with 5 (five) dimensions used to analyze the quality of service delivery from the customer side. The method used to analyze the results of the Service Quality survey is Importance Performance Analysis (IPA).The result of analysis, author Proposed Developing New Business in TOD M1 Soekarno-Hatta International Airport based on the most commercial facility needed by TOD M1 user, andImproving Current Facilities Based on Importance-Performance Analysis.Keywords: Non-Aeronautical Revenue, Company Strategic Objective, Transit Oriented Development (TOD) M1 Soekarno-Hatta International Airport, Developing New Business, Improving Existing Facilities